Building Customer Loyalty Through Product Quality and Customer Satisfaction - Robi Sambung; Ray Julian Kusdiantoro, Aloysius (Optima Science, 2023)
Global market pressure has led all modern companies, including restaurants, to survive the competition by understanding the determinant factors such as product quality, customer satisfaction and customer loyalty. The objective of this research is to find out the effect of product quality on customer loyalty with mediation of customer satisfaction. Design and type of this research are quantitative and explanatory. The object of this research comprises product quality, customer satisfaction and customer loyalty. Subject or also population of this research is the customers of a restaurant named Kuliner Dhahar Enak. Data type is quantitative with the source from primary and secondary data. Sampling technique is Slovin Equation with sample of 78 persons. Data collection technique is questionnaire to get information from respondents. Questionnaire as research instrument is tested with validity test and reliability test. Data analysis procedure employs descriptive statistic analysis, inferential statistic analysis, mediation test, and hypothesis test. Research software involves Microsoft Excel and SmartPLS version 3. Four hypotheses are proposed. The results of research show that product quality has significant effect on customer satisfaction, product quality has significant effect on customer loyalty, customer satisfaction has significant effect on product quality, and product quality significantly affects customer loyalty with mediation of customer satisfaction.